2017
DOI: 10.1121/1.4998572
|View full text |Cite
|
Sign up to set email alerts
|

Scale-sensitivity: A cognitive resource basic to music perception

Abstract: A tone-scramble is a rapid, randomly ordered sequence of pure tones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(47 citation statements)
references
References 44 publications
(48 reference statements)
9
37
0
1
Order By: Relevance
“…On average, trained musicians have higher scalesensitivity than non-musicians. In particular, both Chubb et al (2013) and Dean and Chubb (2017) observed fairly strong correlations between years of musical training and performance in the tone-scramble task. However, a plausible hypothesis is that these correlations are driven primarily by a self-selection bias: listeners with high levels of scalesensitivity tend to seek out musical training whereas listeners with low levels of scale-sensitivity do not.…”
Section: A Musical Training and Scale-sensitivitymentioning
confidence: 93%
See 4 more Smart Citations
“…On average, trained musicians have higher scalesensitivity than non-musicians. In particular, both Chubb et al (2013) and Dean and Chubb (2017) observed fairly strong correlations between years of musical training and performance in the tone-scramble task. However, a plausible hypothesis is that these correlations are driven primarily by a self-selection bias: listeners with high levels of scalesensitivity tend to seek out musical training whereas listeners with low levels of scale-sensitivity do not.…”
Section: A Musical Training and Scale-sensitivitymentioning
confidence: 93%
“…In each of Chubb et al (2013) and Dean and Chubb (2017), the positive correlation between years of musical training and scalesensitivity was driven primarily by a large group of listeners with no musical training who had very little scale-sensitivity as well as a smaller group with many years of musical training who had high scale-sensitivity. Strikingly, however, Chubb et al (2013) and Dean and Chubb (2017) also observed moderate numbers of listeners with many years of musical training with little or no scale-sensitivity as well as other listeners with little or no musical training who had high scale-sensitivity, suggesting that musical training is neither necessary nor sufficient to attain high levels of scalesensitivity. It should be noted, however, that in the study of Dean and Chubb (2017), the highest levels of scale-sensitivity were achieved only by listeners with at least four years of musical training.…”
Section: A Musical Training and Scale-sensitivitymentioning
confidence: 99%
See 3 more Smart Citations